Type I interferon dysregulation in Systemic Sclerosis. (August 2020) - Skaug, Brian; Assassi, Shervin
Abstract: Systemic Sclerosis (Scleroderma, SSc) is a multifaceted disease characterized by autoimmunity, vasculopathy, and fibrosis affecting the skin and internal organs. Despite advances in the understanding and treatment of SSc in recent years, SSc continues to cause reduced quality of life and premature mortality. Type I interferons (IFNs), a family of cytokines with essential roles in the immune response to microbial infection, play a pathogenic role in certain autoimmune diseases (reviewed elsewhere in this edition). Polymorphisms in interferon-regulatory factors confer an increased risk of SSc, and IFN excess is evident in the blood and skin of a large percentage of SSc patients. Here we describe the evidence of Type I IFN dysregulation in SSc, revealed predominately by genetics and gene expression profiling. We also discuss evidence regarding mechanisms by which Type I IFN might contribute to SSc pathogenesis, mechanisms driving excess Type I IFN production in SSc, and the potential roles of Type I IFNs as biomarkers and therapeutic targets in SSc.